Non‐neutralizing antibodies protect against chronic LCMV infection by promoting infection of inflammatory monocytes in mice. Issue 6 (19th February 2021) - Stoycheva, Diana; Sandu, Ioana; Gräbnitz, Fabienne; Amorim, Ana; Borsa, Mariana; Weber, Stefan; Becher, Burkhard; Oxenius, Annette
Abstract: Antibodies play an important role in host defense against microorganisms. Besides direct microbicidal activities, antibodies can also provide indirect protection via crosstalk to constituents of the adaptive immune system. Similar to many human chronic viral infections, persistence of Lymphocytic choriomeningitis virus (LCMV) is associated with compromised T‐ and B‐cell responses. The administration of virus‐specific non‐neutralizing antibodies (nnAbs) prior to LCMV infection protects against the establishment of chronic infection. Here, we show that LCMV‐specific nnAbs bind preferentially Ly6C hi inflammatory monocytes (IMs), promote their infection in an Fc‐receptor independent way, and support acquisition of APC properties. By constituting additional T‐cell priming opportunities, IMs promote early activation of virus‐specific CD8 T cells, eventually tipping the balance between T‐cell exhaustion and effector cell differentiation, preventing establishment of viral persistence without causing lethal immunopathology. These results document a beneficial role of IMs in avoiding T‐cell exhaustion and an Fc‐receptor independent protective mechanism provided by LCMV‐specific nnAbs against the establishment of chronic infection. Abstract : LCMV‐specific non‐neutralizing antibodies (nnAbs ) bind preferentially inflammatory monocytes (IMs ) and enhance their infection . Infected IMs acquire a phenotype of activated antigen‐presenting cells and boost early CD8 T‐cell priming . This supports early effector T‐cell differentiation which contributes to eliminate virus‐infected cells and prevents the establishment of chronic infection .